"OTRA VEZ, REINGENIERÍA 1 2 3, OTRA VEZ" - Téllez Gárate, Antonio (1997)
Case study about an information technology company, dedicated to the assembly, sale and installation of personal computers, and the development of software and multimedia products, which over time had grown and expanded its business lines.  The company implemented a reengineering process to achieve improvements in methods and systems, but the expected results were not obtained, so a specialist was hired who decided to implement new changes based on the analysis of the processes. However, the results obtained were not as expected either, since the company remained the same or worse than before: profits fell compared to previous years, costs increased, customer dissatisfaction was widespread, and new companies were entering the market. In conclusion, the reengineering applied was not working. It was then thought necessary to develop a strategy on how to survive and grow in the short, medium and long term, and to initiate a new reengineering process. The description of the processes and the different areas of the company is included.